Non-corporeal Beings in Iamblichus' Chaldean Doctrine and in Mesopotamia - Mander, Pietro (Studi e materiali di storia delle religioni, 2011)
Broze and Liefferinge had recently pinpointed that the most ancient and therefore authoritative of the three forms of divine knowledge Jamblichus figured out in his De Mysteriis Ægyptiorum is the Chaldean one. As a matter of facts, the key concepts of Jamblichus' treatise match tenets in Mesopotamian religious thought. In the present paper is given a list of the most relevant correspondences. (English)